Missi Al-Qur'an Prespective Fazlur Rahman: Study of the verses of the Quran in the book Major Themes Of The Qur'an Approach Maqāṣid al-Qur’ān - Affandi, Ahmad Rizki (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The Islamic treatises contained in the Qur'an function as a religion that brings grace to the whole world. However, how can the mission of this Qur'anic treatise be realized? Is the achievement optimal? History records that the mission of the treatises of the Qur'an was once fully accomplished at a certain time. This research aims to explore Fazlur Rahman's views on the mission of the Qur'an as described in his book Major Themes of The Qur'an, as well as explain his views on the mission from the perspective of Maqāṣid al-Qur’ān. This type of research is a literature research with the Maqāṣid al-Qur’ān approach. This approach aims to not only get stuck in the context of past texts, but also appreciate the meanings contained in the main texts. To analyze the data, the author applies a critical-analysis research method, which presents information systematically, objectively, and critically. The results of the study show that the mission of the Qur'an according to Fazlur Rahman is the process of applying the meaning of Allah's message contained in the Qur'an, through the development of the rational potential that exists in a believing Muslim, while trying to get closer to the Qur'an without distance.